ANALISIS KEMAMPUAN KOMUNIKASI SISWA SMP DALAM MENYELESAIKAN SOAL AKM NUMERASI BERDASARKAN GAYA BELAJAR - Hayati, Nurul; Fajriana, Fajriana; Rohantizani, Rohantizani (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study aims to analyze students' communication skills in solving the minimum numeracy competency assessment questions based on learning styles and to determine whether there is a relationship between students' communication abilities based on learning styles. This study uses a quantitative approach to the type of correlation research. The subjects of this study were students of class VIII SMP Negeri 1 Lhokseumawe T.A. 2021/2022. The data analysis technique is descriptive analysis. The results showed that the communication skills of students with a visual learning style reached 83.33%. These results are in the very good category, where students are able to use various kinds of numbers or symbols related to basic mathematics in solving life problems. Students with an auditory learning style achieve 73.61% are in a good predicate, where students are able to analyze information displayed in various forms (pictures and so on). Furthermore, the achievement of students with kinesthetic learning styles, namely 74.30%, is in the good category. Students are already able to interpret the results of analysis to predict and make decisions, using their own words. There is no significant relationship between visual learning styles and students' mathematical communication skills in solving Numerical questions. Then for the auditory learning style with communication skills there is no significant relationship between auditory learning style and students' mathematical communication skills in solving Numerical questions. Meanwhile, for kinesthetic learning styles and communication skills, there is no significant relationship between kinesthetic learning styles and students' mathematical communication skills in solving Numerical Assesment.